Mitigation of ferroresonance in power transmission system using series compensator - Abdul Malek, Zulkurnain (2012)
Nowadays power quality becomes critical issue in power electrical system. The connection of three-phase transformer through underground cables is growing fast in residential, commercial, industrial and rural applications. Due to this increasing situation, the possibilities of having a series connected capacitance and a non-linear inductance, prone to ferroresonance, become more probable. Not only the cable capacitance (and consequently its length) is an important factor to take into consideration in the transformers ferroresonance, but also other elements are completely necessary for ferroresonance to appear. All these factors affect the ferroresonance appearance in several ways, producing the phenomenon just as well as making some damaging consequences appear. Because of that, it is necessary to have a general idea about what would be the best preventive decisions to take in order to avoid unexpected surprises. First of all it is necessary to have accurate model consist of ferroresonance then we should apply any device to smooth the sharp effect of it. In this project one of the FACTS devise has been applied, static synchronous series compensator (SSSC) to palliate ferroresonance. It is shown that the performance of system becomes better than before and maintain at its acceptable rated value.